THE PERCEPTION OF FISH FARMER TOWARD UTILIZATION OF EX QUARRY SAND LAND FOR AQUACULTURE BUSSINESS AT UJUNGBATU VILLAGE UJUNGBATU DISTRICT ROKAN HULU REGENCY RIAU PROVINCE - Elsa Christyn Gultom; Ridar Hendri; Kusai ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conduted on September 2015 in the Ujungbatu Village,District of Ujungbatu that located in Regent of RokanHulu Riau Province. Thisresearch was determined purposively with survey method. The respondents wastaken by census amounting to 12 people. The purpose of this researchwere1)toknowfish farmers characteristics in the Ujungbatu Village, 2) to know perceptionsof fish farmer of ex quarry sand land utilization for aquaculture business, 3) and toknow relationship fish farmer characteristics between perception of fish farmerthe ex quarry sand land utilization used the Spearman Rank CorrelationCoefficienttest.The results of this research indicated that the fish farmer perceptions of theex quarry sand land utilization as a whole was in the category of